PENENTUAN KADAR BESI DI DALAM AIR SUMUR GALI PENDUDUK DI DESA KAMPUNG LALANG SECARA SPEKTROFOTOMETRI SINAR TAMPAK - Thaib, Cut Masyithah; Sinaga, Eka Margaret; Purba, Dina Riani (Jurnal Farmanesia, 2019)
Water is one of the sources of iron compound contaminants and the iron content in dug well water used as a water source is influenced by location and environment. The purpose of this study was to determine the iron content in dug well water used in daily life in the village of Kampung Lalang. Samples were taken from five different dug wells. Determination of iron content was carried out according to the spectrophotometric method in accordance with the procedures and spectrophotometers used in the chemical laboratory of the University of Sari Mutiara Indonesia. The results showed that of the 5 samples tested there were 2 samples containing iron compounds exceeding the levels of iron compounds set by the Ministry of Health of the Republic of Indonesia Number 907/MENKES/SK/VII/2002, the permissible levels of iron compounds, which should not be more than 0.3 mg/day. l. The iron content of 5 wells ranged from 0.2457 - 0.405 mg/l.